The Pursuit of Equity in Brazilian Higher Education - Tessler, Leandro (International Higher Education, 2011)
The Brazilian Supreme Court is about to decide if affirmative action complies with the National Constitution. In 2003 the Senate of the University of Brasília (UnB) decided to reserve 20% of its places to black and brown ("pardo") candidates starting in the 2004 admission process. In 2009, the right wing Democratas political party filed a lawsuit at Brazilian Supreme Court claiming that UnB's racial quota system violates no less than nine fundamental precepts of the Constitution. The decision about this case, will determine the future of affirmative action in Brazil. Amazingly all assessments "prove" that affirmative action is neither the deliverance or a threat to the Brazilian higher education system.